Nitrogen and Phosphorus Fertilizers Improve Growth and Leaf Nutrient Composition of Moringa oleifera - Sokombela, Asanda; Eiasu, Bahlebi K.; Nyambo, Patrick (Frontiers in Sustainable Food Systems, 2022)
Establishing the appropriate agronomic practices like fertilizer application is important for maximizing yield and improving nutritional quality of moringa (Moringa oleifera) leaves. The objective of the presented study was to determine the effects of nitrogen and phosphorus fertilizer rates on plant growth performance and leaf nutrient composition of moringa. The experiment was a 4 x 3 factorial, with four nitrogen levels (100, 200, 300 and 400 kg ha-1) and three levels of phosphorus (40, 80 and 120 kg ha-1). The experiment was laid out as randomized complete block design (RCBD), treatments were replicated four times. Twelve weeks after planting, the moringa trees treated with 100 kg N ha-1 and 80 kg P ha-1 were significantly taller by 46.8% than trees supplied with 400 kg N ha-1and 120 kg P ha-1. Similarly, trees that received 100 kg N ha-1and 80 kg P ha-1, and those treated with 200 kg N ha-1 and 80 kg P ha-1 had significantly greater stem diameter (>36%) compared to moringa trees that received 400 kg N ha-1 and 40 kg P ha-1. Crude protein was significantly higher by 26.3% in the 400 kg N ha-1 and 120 kg P ha-1 treatment combination than that of the 100 kg N ha-1 and 40 kg P ha-1 treatment combinations. Moringa trees that received 100 kg N ha-1and 40 kg P ha-1 had the highest neutral detergent fiber content (30.71%), while the trees that received 400 kg N ha-1 and 120 kg P ha-1 had the lower neutral detergent fiber content of 22.77%. Based on the study, the combination of 100 kg N ha-1and 80 kg P ha-1 can be recommended for maximum yield and nutritional content of moringa leaves.